METODE PEMBAHARUAN FIQH AL-NISA’ FEMINIS PESANTREN Studi atas Rekonstruksi Fiqh al-Nisa' pada Kelompok Pesantren - Tutik Hamidah (lp2m-uin malang, 2010)
This research is a library research using phenomenological approach to enable the researcher to grasp the object as it is. The primary sources of this research are representative books by pesantren feminists, such as, Masdar Mas’udi, Islam Hak-Hak Reproduksi Perempuan. Dialog Fikh Pemberdayaan (1997), K.H. Husein Muhammad, Fiqh Perempuan. Refleksi Kiai atas Wacana Agama dan Gender (2001), Syafiq Hasyim, Hal-Hal Yang Tak Terpikirkan dalam Fikih Perempuan (2001), Siti Musdah Mulia, Islam Menggugat Poligami (2004), Maria Ulfah Anshor, Fikih Aborsi. Wacana Penguatan Hak Reproduksi Perempuan (2006). To analyze the data, the researcher uses critical and comparative method.The results of this research are (1) in reconstructing fiqh al-nisa, pesantren feminists used four methods; firstly, in understanding the Quran and Hadith, they divide Islamic teachings into two categories, i.e. universal principles (kulliyyat) and operative principles (juz’iyyat). The former signify qath’i (definitive), and the latter dzanni (speculative); secondly, universal principles become a basis to comprehend operative principles, adding it to several other principles, such as the principle of justice, gender equality, deliberation, well-mannered marital relationship (mu’asyarah bi al-ma‘ruf), and mutual help (ta‘awun); thirdly, operative principles allow any changes in accordance with universal principles and its moral value; fourthly, the method used in this research is twofold: understanding the Quran and Hadith in accordance with opinions of exegetes and jurists of both classical and modern period, and using kulliyat and juziyyat analysis and the approach of social science. (2) Method of pesantren feminists proves to be a continuity of Syatibi’s theory on kulliyat and juziyyat; the widening scope of universal principles reiterates Ibn Taymiyyah’s ideas of maslahah; changing the law by emphasizing maslahah (public interest) is identical with al-Thufi’s theory, rendering opinions of exegetes and jurists as the basis for understanding the Quran and Hadith is tantamount to method of Nahdlatul Ulama at Lembaga Bahtsul Masa’il; employing social sciences and kulliyat and juziyyat analysis is parallel with Sahal Mahfudh’s concept of contextual reading on classical fiqh books.